Toxicity and transport of nanoparticles in agriculture: effects of size, coating, and aging - Islam, Shahidul (Frontiers in Nanotechnology, 2025)
The increasing application of engineered nanoparticles (ENPs) in agriculture for enhanced crop production and protection has raised significant concerns about their environmental fate and potential toxicity. This review examines how particle size, surface coating, and aging influence the transport and toxicity of nanoparticles in agricultural ecosystems. Smaller nanoparticles exhibit greater mobility and reactivity, often leading to increased plant uptake and potential phytotoxic effects, including reduced germination, root inhibition, and oxidative stress. Surface coatings, such as polyethylene glycol (PEG) or natural organic matter, play a crucial role in modulating nanoparticle behavior by stabilizing dispersion, altering bioavailability, and mitigating toxicity. As nanoparticles age in the environment, processes like sulfidation, oxidation, and biotransformation modify their physicochemical properties, often reducing their toxicity but complicating their long-term environmental behavior. The interaction of these variables with soil properties, microbial communities, and plant systems underscores the complexity of nanoparticle dynamics in agricultural settings. While laboratory studies have provided valuable insights, long-term field data and assessments under realistic agrarian conditions remain limited. A better understanding of these factors is essential for predicting environmental impacts and guiding the development of safer and more sustainable nanotechnologies in agriculture. The increasing use of nanoparticles (NPs) in various industrial and consumer applications has led to their inevitable release into agricultural ecosystems. This review article explores the environmental fate, transport, and toxicity of NPs in agroecosystems, emphasizing how particle size, surface coating, and aging influence their interactions with soil, water, plants, and microorganisms. Mechanistic insights, recent findings, and knowledge gaps are discussed to inform safer nanoparticle design and sustainable agricultural practices.